2015
DOI: 10.1158/1078-0432.ccr-14-1717
|View full text |Cite
|
Sign up to set email alerts
|

13C-MR Spectroscopic Imaging with Hyperpolarized [1-13C]pyruvate Detects Early Response to Radiotherapy in SCC Tumors and HT-29 Tumors

Abstract: Purpose: X-ray irradiation of tumors causes diverse effects on the tumor microenvironment, including metabolism. Recent developments of hyperpolarized 13 C-MRI enabled detecting metabolic changes in tumors using a tracer [1-13 C]pyruvate, which participates in important bioenergetic processes that are altered in cancers. Here, we investigated the effects of X-ray irradiation on pyruvate metabolism in squamous cell carcinoma (SCCVII) and colon cancer (HT-29) using hyperpolarized 13 C-MRI. Experimental Design: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 38 publications
2
56
0
Order By: Relevance
“…The advantages of this approach have been outlined by a recent work that substantiated both the solid tumor response and the effects of radiotherapy on healthy tissue in order to survey potential radiation toxicity for areas surrounding the targeted tumor. The response of different types of cancer to therapy has also been monitored using hyperpolarized magnetic resonance, notably in glioma and squamous cell carcinoma . This latter type of cancer is one of the first likely targets for radiotherapy based on short‐pulse lasers with particles of low energy.…”
Section: Molecular Imaging: Early Detection For High Dose‐rate Effectsmentioning
confidence: 99%
“…The advantages of this approach have been outlined by a recent work that substantiated both the solid tumor response and the effects of radiotherapy on healthy tissue in order to survey potential radiation toxicity for areas surrounding the targeted tumor. The response of different types of cancer to therapy has also been monitored using hyperpolarized magnetic resonance, notably in glioma and squamous cell carcinoma . This latter type of cancer is one of the first likely targets for radiotherapy based on short‐pulse lasers with particles of low energy.…”
Section: Molecular Imaging: Early Detection For High Dose‐rate Effectsmentioning
confidence: 99%
“…The use of positron emission tomography (PET) 36 , 13C labeled metabolites such as 13C-pyruvate 37 , and cation exchange saturation transfer (CEST) imaging 38 may be able to allow investigators and clinicians to image altered glucose uptake, energy production, and glutamate neurotransmitter fluctuations, respectively, in acute and late toxicities.…”
Section: Imaging Cns Radiation Effectsmentioning
confidence: 99%
“…Another study used metabolism of hyperpolarized 13 C-pyruvate as a marker of response to temozolomide treatment in glioblastoma multiforme cells [155]. Additionally, preclinical studies have shown promise for the use of hyperpolarized 13 C-pyruvate MRS imaging for evaluating radiation treatment response [156] and to assess response to hypoxia-sensitizing drugs [157]. With the variety of available 13 C-labeled substrates, hyperpolarized 13 C MRS imaging may prove to be a powerful tool for visualization of numerous cancer-related metabolic processes for early assessment of treatment response.…”
Section: Correlation Between Tumor Vascularization and Treatment Respmentioning
confidence: 99%